Simulation Analysis of the Forming Process of Tapered Multi-blade Scraper Tool - Guo Erkuo; Ren Naifei; Wang Jie; Zhou Changlu (Jixie chuandong)
Numerical control power skiving is a modern and productive method in the manufacturing of cylindrical gears. Aiming at the problem of short service life of single-edge tool in powerful tooth skiving technology, a novel skiving tool with multiple blades with higher efficiency is proposed. Based on the meshing theory of crossed axes and the cutting process of tooth surface in gear skiving, the kinematics model of powerful tooth scraping and the cutting model of tapered multi-edge cutter are established. By using the machining simulation software, a simulation method for the analysis of the forming process of multi-blade gear cutters, simulation model setting and simulation cutting procedure are given. By comparing the simulation cutting results, the similarities and differences between multi-blade and single-blade are analyzed, and the feasibility of tapered multi-blade skiving tool is verified. The study results provide the theory basis for the productive generating mechanism of cylindrical gears and the development of multi-blade skiving tool.